Unlocking the Potential of Cecostomies: A Valuable Lifesaving Procedure in Emergency Surgery for Colonic Obstructions - Constantin Popazu; Alexandra Toma; Daniela Mihalache; Oana-Monica Duca; Dorel Firescu; Dragoș F. Voicu (Life)
Background: Colonic obstructions present a serious medical emergency that requires prompt surgical intervention to prevent life-threatening complications. Cecostomy, a procedure involving the creation of an opening in the cecum to decompress the colon, serves as one surgical approach for managing these obstructions. The aim of this review is to evaluate the effectiveness and benefits of cecostomies in emergency surgical settings, with a focus on recent clinical studies and case reports. Cecostomy is highlighted as a bridge procedure in cases such as obstructive carcinomas, providing data on success rates, relative survival, and clinical effectiveness. The importance of the patient’s condition and surgeon expertise in selecting cecostomy as a procedure is emphasized. Further comparative research is suggested to optimize the selection criteria, providing a strong, clinically oriented conclusion. Methods: A comprehensive literature review was conducted to identify studies and case reports focusing on the application of cecostomies in cases of acute colonic obstruction. Articles were selected based on their relevance to emergency surgery, the effectiveness of cecostomies, and patient outcomes in various clinical scenarios, including obstructive carcinomas and colonic pseudo-obstructions. Results: The analysis reveals that cecostomies provide rapid decompression and effective relief from colonic obstruction, particularly when immediate intervention is needed to prevent bowel perforation or ischemia. In several cases, cecostomies act as a bridge to more definitive surgical treatments, such as resection and anastomosis, and are associated with reduced morbidity and mortality. The selection of cecostomy as a preferred procedure depends on the patient’s condition, location of the obstruction, and surgeon expertise. Conclusions: Cecostomies play a crucial role in the emergency management of colonic obstructions, offering a viable and sometimes lifesaving alternative for rapid decompression. Understanding the indications and appropriate use of cecostomies can enhance patient outcomes and provide surgeons with effective strategies for managing acute colonic obstructions. Further research is warranted to refine selection criteria and to compare outcomes between cecostomies and other decompressive techniques in emergency settings.